Detection and Treatment of Hyperuricemia in Clinical Practice (According to the PROFILE Outpatient Registry) - N. P. Kutishenko; S. Yu. Martsevich; A. V. Zagrebelnyy; Yu. V. Lukina; V. P. Voronina; N. A. Dmitrieva; O. V. Lerman; S. N. Tolpygina; S. V. Blagodatskikh; I. V. Budaeva; E. S. Nekoshnova; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
Aim. To study the frequency of detection of hyperuricemia (HU) in patients with high and very high cardiovascular risk and the frequency of prescribing drugs that lower serum uric acid (sUA) levels in real clinical practice.Material and methods: The general information of the study was based on the data of 2457 patients who were consistently included in the «PROFILE» registry until November 30, 2020: 1250 men (50.9%) and 1207 (49.1%) women. All patients with HU were selected (UA level ≥360 pmol/l in women, ≥420 pmol/l in men). At the stage of inclusion of the patient, data on MC indicators were available in 1777 (72.3%), upon re-examination - only 262 (33.2%) out of 790 patients who returned to the appointment.Results: The most common study of the level of sUA was performed in patients with gout (65.2%), with arterial hypertension (AH) and dyslipemia in 29.1% of cases, with diabetes mellitus (DM) - 30.1%, with impaired tolerance to glucose (IGT) - 40.2%, with other diseases, the proportion of patients with a known UA was even less. A positive relationship was found between the presence of AH and IGT with the frequency of UA control (p<0.001). In patients with AH, an increase in the level of sUA was detected significantly more often than in patients without AH (p<0.001), and less frequently in patients with DM and IGT (p<0.001 and p<0.01, respectively). The frequency of allopurinol prescribing was low: 49 (2%) patients received therapy, while of the 284 patients with HU, only 20 (7%) were prescribed allopurinol.Conclusion: in real clinical practice, only 29.1% of patients with AH and 20-25% of patients with other CVDs were monitored for sUA levels, every third patient had data on sUA levels at a repeat visit. In the presence of gout, the proportion of patients with current UA was higher (65%). For those with AH and IGT, positive correlations were found between the presence of the disease and control of sUA levels. A low frequency of prescribing drugs for the correction of HU was revealed.